Behavioral Tendency to Choose Sharia Bank Among College Students - Novianti, Dian; Sari, Erna Juwita; Arifin, Andi Putri Maharani; Akila, Nur; Agit, Alamsyah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The purpose of this paper is to examine and explore the factors that could influence behavioral tendency of potential client to choose sharia banks and existing client to loyal toward sharia banks, the paper focuses on college student of STAI DDI Sidenreng Rappang, which located in the regency of Sidenreng Rappang of South Sulawesi Province. This paper employs a qualitative approach, using a case study. This paper gathers data through open interview, which is to explore the factors that influence behavioral tendency to choose sharia banks among college students. The result of this paper indicates that there are three main aspect that influence college student to choose sharia banks, which is knowledge, since the student of STAI DDI Sidenreng Rappang, learn so much about the Islamic education, one of it explains the Islamic ethic in conducting business, further promotion factor also plays important role, as some student states that some of them choose sharia banks because they know, but some also stated that they didn’t know, which is why they didn’t use sharia banks service, indicating promotion plays important role in order to gain clients. The finding of this paper indicates promotion factor plays important role in influencing tendency to choose sharia banks, which this serves as critique and recommendation for sharia banks, to develop more aggressive strategies and approach to promote their firm. The Originality of this paper is the random takes on exploring probability of numerous factors that may influence tendency to choose sharia bank, while some research determines their focuses on what aspect they about dive in, this paper discovers the factor that influence behavioral tendency to choose sharia bank throughout the process of this research.